Detection of Herpes Simplex Virus 1 and 2 in Semen, Blood and Urine of Idiopathic Infertile Men and Its Association with Sperm Count and Motility - Marzieh Tajedini; Mohammad Ali Sadighi Gilani; Tahere Heydari; Kolsoom Choobineh; Hamid Choobineh (Tehran University of Medical Sciences, 2017)
Background and Aim: Infertility is a major problem of modern medicine as it affects almost 20% of reproductive-aged couples. The cause of this problem is attributed to the male partner in nearly 40%-50% of these cases. The role of herpes simplex virus (HSV) in male infertility has been investigated using the sensitive methods. The aim of this study was to determine the prevalence of HSV-1, 2 DNA in the semen, blood and urine of idiopathic infertile men and its association with altered semen parameters. Materials and Methods: A total of 150 semen, blood and urine samples from infertile men were collected in the Shariati hospital, Tehran (2012-2014). Sample analysis and diagnostic PCR using specific primers was performed for detection of HSV-1, 2 DNA in the specimens. Results: Analysis showed six groups of infertile men, including HSV-1, 2 positive and negative groups in semen, blood and urine samples. HSV-1, 2 DNA was detected in 38 (18.66%) semens, (6.66%) 10 in blood and 2 (1.33%) in urine. Only HSV-1, 2 positive samples of semen had abnormal semen parameters. Conclusion: Using a powerful molecular method, we detected a high prevalence of HSV-1, 2 DNA in the semen of asymptomatic infertile patients. Although HSV-1, 2 infections were not associated with motility and morphology defects of the sperms, it was related with decreased sperm count in the semen fluid. In addition there was not a significant role for detection of HSV-1, 2 DNA in blood and urine samples of infertile men and abnormal semen parameters.